Improving the utilization of lignocellulosic biomass by polysaccharide modification. Issue 2 (February 2016) - Damm, Tatjana; Commandeur, Ulrich; Fischer, Rainer; Usadel, Björn; Klose, Holger
Highlights: Transgenic biomass offers a promising alternative resource for fuels and chemicals production. In planta enzyme expression could efficiently modify plant cell walls. Modification of cell walls in planta may allow more efficient processing of plant biomass for industrial applications. Abstract: Lignocellulosic biomass offers an economically sustainable renewable source of chemicals and fuels, but the development of efficient processes for lignocellulose utilization is challenging due to the complex and heterogeneous structure of plant cell walls. Transgenic plants expressing recombinant proteins that promote cell wall modification or deconstruction could facilitate the digestion of lignocellulose, and enzymes that facilitate the degradation of polysaccharides in particular could improve the industrial production of fibres, textiles, pulp, paper, chemicals and fuels. In this review we summarize what is known about plant cell wall architecture and discuss current strategies to improve plants by expressing recombinant proteins that facilitate the degradation of cell wall carbohydrates. We compare the ability of these different approaches to simplify the processing of lignocellulose and showcase particularly comprehensive approaches and the future perspectives of these technologies.